Investigating the effect of gamma-ray interaction on the stability and physicochemical properties of turmeric and ginger using Monte Carlo simulation - KILIÇOĞLU MEHMETCİK, ÖZGE (My University, 2022)
Turmeric and ginger are among the most widely used medicinal plants due to their health benefits and bio-activities, which include antiviral and antioxidant properties. However, these plants are usually irradiated to increase their shelf life and quality. Using a Monte Carlo simulation, this study investigates the structural changes in the active ingredients of ginger and turmeric after irradiation. The Linear Attenuation Coefficient (LAC) and Mass Attenuation Coefficient (MAC) calculations are interrelated with the properties of materials in terms of low and high radiation absorption. According to the results, curcumin showed better absorption attributes compared to 6-gingerol. The results also indicated an increase in the total antioxidant activity and b value (yellowness) of turmeric after treatment with 5 kGy irradiation. On the other hand, positive correlations were also found be-tween MAC and ABTS values. It can be concluded that irradiation up to 5 kGy dosages could be beneficial for turmeric as it both prevents microbial contamination and increases its antioxidant activity. However, the results indicated that the effect of irradiation on the antioxidant activity varies depending on the nature of the product, thus further studies are required to better understand the effect of irradiation on the bioactive components of food materials.
Keywords: Fizik; Atom ve Molekül Fiziği; Nükleer Fizik; Kimya; Fizikokimya; Temel Bilimler; Physics; Atomic and Molecular Physics; Nuclear physics; Chemistry; Physical Chemistry; Natural Sciences; KİMYA, FİZİKSEL; Temel Bilimler (SCI); NÜKLEER BİLİMİ VE TEKNOLOJİSİ; FİZİK, ATOMİK, MOLEKÜLER VE KİMYASAL; CHEMISTRY, PHYSICAL; CHEMISTRY; Natural Sciences (SCI); NUCLEAR SCIENCE & TECHNOLOGY; PHYSICS; PHYSICS, ATOMIC, MOLECULAR & CHEMICAL; Yüzeyler ve Arayüzler; Radyasyon; Atom ve Moleküler Fizik ve Optik; Yüzeyler, Kaplamalar ve Filmler; Nükleer Enerji ve Mühendislik; Fiziksel ve Teorik Kimya; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Surfaces and Interfaces; Radiation; Atomic and Molecular Physics, and Optics; Surfaces, Coatings and Films; Nuclear Energy and Engineering; Physical and Theoretical Chemistry; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Gamma-irradiation; Turmeric; Ginger; Antioxidant activity; Monte Carlo simulation; ANTIOXIDANT ACTIVITY; IRRADIATION; EXTRACTION; QUALITY